Detection and localization of calcium oxalate in kidney using synchrotron deep ultraviolet fluorescence microscopy. (12th December 2021) - Estève, Emmanuel; Buob, David; Jamme, Frédéric; Jouanneau, Chantal; Kascakova, Slavka; Haymann, Jean-Philippe; Letavernier, Emmanuel; Galmiche, Louise; Ronco, Pierre; Daudon, Michel; Bazin, Dominique; Réfrégiers, Matthieu
Abstract : Synchrotron deep ultraviolet imaging highlighting pathological calcium oxalate detection in kidney is presented. Abstract : Renal oxalosis is a rare cause of renal failure whose diagnosis can be challenging. Synchrotron deep ultraviolet (UV) fluorescence was assayed to improve oxalosis detection on kidney biopsies spatial resolution and sensitivity compared with the Fourier transform infrared microspectroscopy gold standard. The fluorescence spectrum of synthetic mono‐, di‐ and tri‐hydrated calcium oxalate was investigated using a microspectrometer coupled to the synchrotron UV beamline DISCO, Synchrotron SOLEIL, France. The obtained spectra were used to detect oxalocalcic crystals in a case control study of 42 human kidney biopsies including 19 renal oxalosis due to primary (PHO, n = 11) and secondary hyperoxaluria (SHO, n = 8), seven samples from PHO patients who received combined kidney and liver transplants, and 16 controls. For all oxalocalcic hydrates samples, a fluorescence signal is detected at 420 nm. These spectra were used to identify standard oxalocalcic crystals in patients with PHO or SHO. They also revealed micrometric crystallites as well as non‐aggregated oxalate accumulation in tubular cells. A nine‐points histological score was established for the diagnosis of renal oxalosis with 100% specificity (76–100) and a 73% sensitivity (43–90). Oxalate tubular accumulation and higher histological score were correlated to lower estimated glomerular filtration rate and higher urinary oxalate over creatinine ratio.